2014
DOI: 10.1523/jneurosci.1765-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography Correlates of Spatial Working Memory Deficits in Attention-Deficit/Hyperactivity Disorder: Vigilance, Encoding, and Maintenance

Abstract: In the current study we sought to dissociate the component processes of working memory (WM) (vigilance, encoding and maintenance) that may be differentially impaired in attention-deficit/ hyperactivity disorder (ADHD). We collected electroencephalographic (EEG) data from 52 children with ADHD and 47 typically developing (TD) children, ages 7-14 years, while they performed a spatial Sternberg working memory task. We used independent component analysis and time-frequency analysis to identify midoccipital alpha (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
155
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(184 citation statements)
references
References 63 publications
22
155
2
Order By: Relevance
“…Importantly, post-training there was a cluster of posterior electrodes that showed significantly greater alpha power for the Sham group compared to the Active group ( p < 0.05); see Figure 5D. Because posterior alpha power increases with WM load (Jensen, et al, 2002; Lenartowicz, et al, 2014; Sauseng, et al, 2009), these results suggest that after training the Active group more efficiently maintained items in WM (Figure 6). …”
Section: 1 Resultsmentioning
confidence: 88%
“…Importantly, post-training there was a cluster of posterior electrodes that showed significantly greater alpha power for the Sham group compared to the Active group ( p < 0.05); see Figure 5D. Because posterior alpha power increases with WM load (Jensen, et al, 2002; Lenartowicz, et al, 2014; Sauseng, et al, 2009), these results suggest that after training the Active group more efficiently maintained items in WM (Figure 6). …”
Section: 1 Resultsmentioning
confidence: 88%
“…The nogo-N2 is considered a candidate endophenotype for alcoholism (Kamarajan & Porjesz, 2015), and similar types of experimental manipulations are likely to inform us about the nature of individual differences in this putative endophenotype. Lenartowicz and colleagues (Lenartowicz et al, 2014) used a visual-spatial version of the Sternberg working memory test in a sample of children with ADHD and typically developing controls to parametrically vary task load and thereby try to isolate the source of the difficulties experienced by children with ADHD. Studies such as these can help to isolate the psychological and neural processes reflected in putative endophenotypes for ADHD such as the P2 ERP component and thus the precise nature of genetic risk reflected in the endophenotype.…”
Section: 0 Where Do We Go From Here?mentioning
confidence: 99%
“…Namely, it was demonstrated that the power of EEG alpha oscillation increased during the early and late phases of creative ideas generation [16]. Alpha band oscillations play an active role in attention and working memory [17,18]. Recent studies using treadmill workstations have demonstrated benefits of walking on performance and cognitive abilities that are necessary for tasks requiring attention and memory [19,20].…”
Section: Walking and Creativity "Un Pas De Deux "mentioning
confidence: 99%